Hubungan Kejadian Hiperglikemia dengan Hipertensi pada Peserta Posyandu Lansia di Desa Kubangsari Brebes - Casyanti, Casyanti; Khusna, Umi Nihayatul (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2026)
Hyperglycemia and hypertension are two common health disorders among the elderly. Persistently elevated blood glucose levels in individuals with diabetes mellitus can lead to various health complications, one of which is hypertension. Therefore, this study aimed to determine whether there is an association between hyperglycemia and hypertension among elderly individuals attending the integrated healthcare post (Posyandu) in Kubangsari Village, Ketanggungan District, Brebes Regency, in 2025. This study employed an analytic observational design with a cross-sectional approach. A total of 80 respondents were included as samples. Random blood glucose levels were measured using a point-of-care testing (POCT) device, while blood pressure was measured using a sphygmomanometer. Quantitative data analysis was performed using the Chi-square test. The results showed that 61 respondents (76.3%) had normal blood glucose levels, and 34 respondents (42.5%) had normal blood pressure. The Chi-square analysis indicated a significance value of p < 0.001, suggesting a statistically significant association between hyperglycemia and hypertension. Based on these findings, it can be concluded that hyperglycemia contributes to the occurrence of hypertension among the elderly. Therefore, routine health examinations are necessary to prevent further complications.